Peran Firma Hukum Dalam Meningkatkan Akses Bantuan Hukum Kepada Masyarakat - Sarah Marissa Aromagira Girsang; Fally Avriantara (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The 1945 NRI Constitution as the Constitution of the Republic of Indonesia has guaranteed equality before the law for everyone, therefore the State guarantees and is obliged to ensure that its citizens have better access to legal aid. The data still displays a difference in the number of Legal Aid Organizations (LOB) and the underprivileged individuals seeking justice. There are thousands of law firms that have been established and spread across the Indonesian territory in both litigation and non-litigation fields, which can be the solution or answer to this inequality. The type of research is juridical-normative and employs a legal approach to research. The interpretation method involves an interpretation-systematic approach that analyzes qualitative data. As for the conclusion reached, (1) The Regulation on the Granting of Legal Aid in Indonesia are based on the provisions of the Herziene Indische Reglement (HIR), Act No. 18 of 1981 on the Law of Criminal Procedure, Act No. 18 of 2003 on Advocates, Act No. 48 of 2009 on Judicial Authority and Act No. 16 of 2011 on Legal Aid. (2) The role of a law firm in improving access to legal aid in the community is to provide legal aid or legal services free of charge as an embodiment of the officium nobile and to cooperate or collaborate with certain local Legal Aid Institutions with the form of tangible activities such as holding legal counseling accompanied by the provision of legal aid services.